Information System Design COVID-19 with Prototype Model - Syahri Susanto; Julifer P. Manurung; Feddy Wnditya Setyawan (Information System; Universitas Buana Perjuangan Karawang, 2020)
Information System Design COVID-19 with Prototype Model